Comprehensive summary and retrospective evaluation of prognostic scores for patients with newly diagnosed brain metastases treated with upfront radiosurgery in a modern patient collective. (July 2022) - Kraft, Johannes; van Timmeren, Janita E.; Frei, Simon; Mayinger, Michael; Borsky, Kim; Kirchner, Corinna; Stark, Luisa Sabrina; Tanadini-Lang, Stephanie; Wolpert, Fabian; Weller, Michael; Woodruff, Henry C.; Guckenberger, Matthias; et al.
Highlights: Comparison of 17 known prognostic scores for patients with brain metastases. Evaluation in 470 patients treated with upfront radiosurgery for brain metastases. Comprehensive performance analysis of all prognostic scores. Performance status alone shows impressive efficacy in overall survival prediction. Abstract: Background: Numerous prognostic scores (PS) for patients with brain metastases (BM) have been developed. Recently, PS based on laboratory parameters were introduced to better predict overall survival (OS). A comprehensive comparison of the wide range of scores in a modern patient collective is still missing. Materials and methods: Twelve PS considering clinical parameters only at the time of BM diagnosis were calculated for 470 patients receiving upfront SRS between January 2014 and March 2020. In a subcohort of 310 patients where a full laboratory dataset was available five additional prognostic scores were compared. Restricted mean survival time (RMST), partial likelihood and c-index were calculated as metrics for performance evaluation. Univariable and multivariable analysis were used to identify prognostic factors for OS. Results: The median OS of the whole cohort was 15.8 months (95% C.I.: 13.4–20.1). All prognostic scores performed well in separating patients into different prognostic groups. RPA achieved the highest c-index, whereas GGS achieved highest partial likelihood with evaluation in the total cohort. With incorporation of the laboratory scores the recently suggested EC-GPA achieved highest c-index and highest partial likelihood. A prognostic score solely based on the assessment of performance status achieved considerable high performance as either 3- or 4-tiered score. Multivariable analysis revealed performance status, systemic disease status and laboratory parameters to be significantly associated with OS among variates included in prognostic scores. Conclusion: Although recent PS incorporating laboratory parameters show convincing performance in predicting overall survival, older scores relying on clinical parameters only are still valid and appealing as they are easier to calculate, and as overall performance is almost equal. Moreover, a score just based on performance status is not significantly inferior and should at least be assessed for informed decision making.